2017
DOI: 10.1371/journal.pone.0174317
|View full text |Cite
|
Sign up to set email alerts
|

Validation of qPCR reference genes in lymphocytes from patients with amyotrophic lateral sclerosis

Abstract: Quantitative polymerase chain reaction (qPCR) is the most specific and reliable method for determination of mRNA gene expression. Crucial point for its accurate normalization is the choice of appropriate internal control genes (ICGs). In the present work we determined and compare the expression of eight commonly used ICGs in lymphocytes from 26 patients with amyotrophic lateral sclerosis (ALS) and 30 control subjects. Peripheral blood mononuclear cells (PBMCs) before and after immortalization by EBV transfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
(37 reference statements)
2
9
0
Order By: Relevance
“…We found that all analyzed RGs could be considered stable according to stability values calculated via the distinct algorithms, although there were some discrepancies according to the patients’ characteristics. These different results depending on the disease are in accordance with the work of Usarek et al, who found that the best RG for healthy PBMCs was B2M , whereas in PBMCs from patients with amyotrophic lateral sclerosis, it was HPRT1 [ 27 ]. Additionally, Wang et al found lower basal expression levels of PPIA in asthmatics than in healthy controls [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…We found that all analyzed RGs could be considered stable according to stability values calculated via the distinct algorithms, although there were some discrepancies according to the patients’ characteristics. These different results depending on the disease are in accordance with the work of Usarek et al, who found that the best RG for healthy PBMCs was B2M , whereas in PBMCs from patients with amyotrophic lateral sclerosis, it was HPRT1 [ 27 ]. Additionally, Wang et al found lower basal expression levels of PPIA in asthmatics than in healthy controls [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…Upregulation of CTSH has also been reported in the spinal cord of SOD1 G93A mice but has not been studied thoroughly ( 59 ). Similarly, upregulated B2M has been reported in the peripheral blood of ALS patients ( 60 , 61 ). ITGB2, C3, C1QA, C1QB, and C1QC were observed as central genes in PPI analysis, and each of them performed an important role in synaptic pruning.…”
Section: Discussionsupporting
confidence: 56%
“…Properdin, as well as Factor D, are the components of the complement system. They act as an activator of the complement system by stabilizing the alternative pathway convertase [ 46 , 47 ]. The alternative pathway of complement activation is associated with many autoimmune diseases, such as arthritis and age-related macular degeneration [ 48 ].…”
Section: Discussionmentioning
confidence: 99%